Perhitungan Saluran Drainase Kopelma Darussalam Kecamatan Syiah Kuala Kota Banda Aceh - Amalia Effendy; Muhammad Ridha (Jurnal Teknik Sipil Unaya, 2018)
Number of Population growth will be effect to urban land use. Housing development will be impact to the urban land use function. Land use changed, city growth and Housing development icreasing if not planning well will be effect to Urban water system. Kopelma Darussalam is an area that have problem like that. In that area, demand to housing development to fulfill house for student and employe increasing by the year. Flat topography cause drainage system that eksist not capable anymore. This research aim to design and calculating the drainage dimension in Kopelma Darussalam. In this research used qualitative method.